Dynamic pricing decisions and seller-buyer interactions under capacity constraints - Vincent Mak; Amnon Rapoport; Eyran J. Gisches (Games, 2018)
Focusing on sellers' pricing decisions and the ensuing seller-buyer interactions, we report an experiment on dynamic pricing with scarcity in the form of capacity constraints. Rational expectations equilibrium solutions are constructed and then tested experimentally with subjects assigned the roles of sellers and buyers. We investigate behavior in two between-subject conditions with high and moderate levels of capacity. Our laboratory market exhibits strategic sophistication: the price offers of sellers and the buyers' aggregate responses largely approximate equilibrium predictions. We also observe systematic deviations from equilibrium benchmarks on both sides of the market. Specifically, in our experiment the sellers are boundedly strategic: their prices often exhibit strategic adjustments to profit from buyers with limited strategic sophistication, but they are also often biased towards equilibrium pricing even when that would not be ex-post optimal.
Keywords: 330; dynamic pricing decisions; scarcity; capacity constraints; strategic seller-buyer interactions; experiments; game theory